Versions of the National Criticism: Two Readings of Arte nuevo at the End of the XIX Century (Anclajes, 2012)
At the end of the nineteenth century, two antagonistic factions disputed the hegemony of the Spanish intellectual field: the orthodox Catholic traditionalism and the Krausist liberalism. In such a significant context, to look for evidences of the theoretical confrontation between Marcelino Menéndez y Pelayo and Manuel de la Revilla acquires real importance when trying to understand the origin of opposing viewpoints between the Hispanic critics. Besides, the readings made by Menéndez y Pelayo and Alcántara García on Lope de Vega’s Arte nuevo helps to illustrate the subject by means of an example with precise resonances.
Keywords: Spanish criticism in the nineteenth century; Marcelino Menéndez y Pelayo; Manuel de la Revilla; Lope de Vega